Pediatric therapy : an interprofessional framework for practice - Thompson, Catherine Rush, 1954-; Coffelt, Ketti Johnson; Hart, Pamela (Associate professor of communication sciences and disorders) (SLACK Incorporated, 2018)
Pediatric Therapy: An Interprofessional Framework for Practice has been designed to engage students and clinicians in interprofessional learning experiences that cultivate collaborative practice and optimize the outcomes of those served.